Carbon dynamics of the Weddell Gyre, Southern Ocean - Brown, Peter J.; Jullion, Loïc; Landschützer, Peter; Bakker, Dorothee C.E.; Naveira Garabato, Alberto C.; Meredith, Michael P.; Torres-Valdés, Sinhue; Watson, Andrew J.; Hoppema, Mario; Loose, Brice; Jones, Elizabeth M.; Telszewski, Maciej; et al. (American Geophysical Union, 2015)
The accumulation of carbon within the Weddell Gyre and its exchanges across the gyre boundaries are investigated with three recent full-depth oceanographic sections enclosing this climatically important region. The combination of carbon measurements with ocean circulation transport estimates from a box inverse analysis reveals that deepwater transports associated with Warm Deep Water (WDW) and Weddell Sea Deep Water dominate the gyre's carbon budget, while a dual-cell vertical overturning circulation leads to both upwelling and the delivery of large quantities of carbon to the deep ocean. Historical sea surface pCO2 observations, interpolated using a neural network technique, confirm the net summertime sink of 0.044 to 0.058 ± 0.010 Pg C yr−1 derived from the inversion. However, a wintertime outgassing signal similar in size results in a statistically insignificant annual air-to-sea CO2 flux of 0.002 ± 0.007 Pg C yr−1 (mean 1998–2011) to 0.012 ± 0.024 Pg C yr−1 (mean 2008–2010) to be diagnosed for the Weddell Gyre. A surface layer carbon balance, independently derived from in situ biogeochemical measurements, reveals that freshwater inputs and biological drawdown decrease surface ocean inorganic carbon levels more than they are increased by WDW entrainment, resulting in an estimated annual carbon sink of 0.033 ± 0.021 Pg C yr−1. Although relatively less efficient for carbon uptake than the global oceans, the summertime Weddell Gyre suppresses the winter outgassing signal, while its biological pump and deepwater formation act as key conduits for transporting natural and anthropogenic carbon to the deep ocean where they can reside for long time scales. ISSN:0886-6236 ISSN:1944-9224